Higher Education, a challenge for Intercultural Community Universities in Latin America - Blandón Jirón, Consuelo Lizeth (Revista Universitaria del Caribe, 2019)
In the first section you will find a brief tour of the context of higher education in Latin America, emphasizing laws, regulations, conventions, political constitution of countries that endorse and recognize indigenous and Afro-descendant peoples. In the second section, a brief tour of some intercultural community universities in Latin America that have been founded with a single purpose it is covered, to rescue endogenous knowledge, to professionally prepare native peoples. The third section, based on the current debate on interculturality, intercultural collaboration in research, a joint contribution with communities, where the way of collaborating from research and the existing linkage for indigenous and Afro-descendant communities is highlighted, so they can enjoy a better life plan, give answers to problems that can be solved from community research.